Evolution of the biological effect of synthesized zinc-iron oxides nanoparticles on organic pollutants in drinking water - H. M. Hussain; M. B. Mahmood; L. A. Yaaqoob (Iraqi Journal of Chemical and Petroleum Engineering)
This study aimed to explain the biosynthesis process of Zinc and Iron oxide nanoparticles (Zn- O+ Fe- ONPs) using an extracellular enzyme, which in turn produced from particular environmental bacteria isolates Escherichia coli a stabilizing and reducing agent. Biosynthesized (ZnO+FeO) nanoparticles have presented many applications such as catalysis, biosensing, anticancer, and biomedical, etc. The optimum condition for Zn-O and Fe-O biosynthesis was characterized through several techniques such as UV-Vis, AFM, XRD, FT-IR, and FE-SEM. In particular, a cut-off phenomenon of the biological synthesized Zn-O and Fe-O was found at around 287 nm using UV-Vis, while spherical shape particles were noticed using FE-SEM techniques. Also, the AFM analysis revealed that Zn-O and Fe-O NPs have an average diameter size of 75.03 nm. Determine the FTIR spectrum of the biosynthesized Zn-O and Fe-O nanoparticles showing Zn-O at the broad peak at 509.17-426.24 cm. Where the study shows the best removal of organic pollutants after using the nano-mix oxides of the following organic pollutants (Henecosaine, Eicosane, Tridecane, Docosane, Tetradecane) The removal percentage was straight (6.13-2,34-0,49-1.87-0,84%). After measuring the drinking water sample before and after using the nanoparticles with the GC-Mass device. The best percentage for removing inorganic pollutants of (Pb, Cr, Cu) after treatment mixture nanoparticles, and the removal percentages were respectively (12.24-1.37-0.44%). As for (Cd, Al) the percentage was respectively (8.11-3.94) after using the nanoparticles with the ICP-EOS device.